Academic Factors Predicting NCLEX-RN Success. Issue 2 (March 2022) - Flowers, Monica; Olenick, Maria; Maltseva, Tatayana; Simon, Sharon; Diez-Sampedro, Ana; Allen, Lois Ryan
Abstract : Supplemental digital content is available in the text. Abstract: This retrospective study examined the relationships among 10 academic predictors and first-time success on the NCLEX-RN in a sample of 92 bachelor of science in nursing minority and culturally diverse generic/traditional students at a large minority-serving, urban, public university. Predictors included the Test of Essential Academic Skills (overall, science, and reading), science grade point average (GPA), cumulative GPA, and scores on various standardized exams: Kaplan, HESI, and ATI. Discriminant analysis found science GPA of >3.50 and ATI B of 60 or above to be the best predictors of passing NCLEX-RN. Based on statistically significant differences between NCLEX-RN pass and fail scores, good indicators of NCLEX-RN success were scores of 50 or above on Kaplan and 950 or above on HESI. Overall, the Test of Essential Academic Skills did not predict students' NCLEX-RN outcomes.